PENGARUH ASIMETRI INFORMASI TERHADAP HUBUNGAN ANTARA PENERAPAN SISTEM PERDAGANGAN DUA PAPAN DI BURSA EFEK JAKARTA DAN INDIKASI MANAJEMEN LABA PADA PERUSAHAAN PERBANKAN - ANIS WIJAYANTO; RAHMAWATI RAHMAWATI; YACOB SUPARNO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2007)
The purpose of this research is to examine the influence of information asymmetry to the relationship between applying of commerce system two board in Jakarta Stock Exchange and earnings management indication at banking firms in BEJ. Results of this research are expected be benefit to BAPEPAM, Indonesian Bank, Investor, Creditor, and academician. The companies taken as sample in the research is banking firms which listed in Jakarta Stock Exchange from 2000-2004. The data pool method is used to collect 120 observation. The hypothesis is tested by regression (OLS). In order to control the size effects, analytical model in the research use the control variable of SIZE and GROWTH, and to control the firms risk use Cash Flow Variance (Cfvar) dan Market to Book Value (Mktbv). The research show that there is no significant influence of information asymmetry to the relationship between applying of commerce system two board in Jakarta Stock Exchange and earnings management indication at banking firms in BEJ, so Ho can not be rejected.This research show that there was significant effect of multyboard policy towards earnings management (research to manufacture and non manufacture emiten, except financial emiten). This research also show that the effect of variable control higher than variable independent multiboard policy.